Comparative transcriptomics and metabolomics in Vitis vinifera 'Malvasia' and Vitis rupestris 'Du Lot' cultured cells provide insights in possible innate resistance against pathogens. (4th May 2021) - Brasili, Elisa; Donati, Livia; Sciubba, Fabio; Ferretti, Luca; Miccheli, Alfredo; Pasqua, Gabriella
Abstract: Grapevine varieties showing putative resistance to pathogens are a promising alternative to reduce the impact of disease management. Despite research efforts in understanding pathogen susceptibility/resistance to pathogens, the mechanisms that regulate these processes remain unclear. To identify the molecular and metabolic mechanisms associated with putative different susceptibility to pathogens and/or constitutive resistance, comparative transcriptomics and metabolomics were carried out in cultured cells of V. vinifera 'Malvasia' and V. rupestris 'Du Lot'. Transcriptomic analysis revealed a higher enrichment of genes involved in biosynthesis of cell wall proteins, PR protein, ROS activation, phenylpropanoid pathway, TIR-NBS-LRR proteins and WRKY transcription factors in V. rupestris compared to V. vinifera . 1 H-NMR based metabolomic analysis highlighted that leucine, isoleucine, valine, threonine, alanine, γ-aminobutyric acid (GABA), glutamine, phenylalanine and pyruvate significantly increased in V. rupestris compared to V. vinifera . Conversely, glucose, sucrose, and fumarate significantly decreased in V. rupestris compared to V. vinifera. Our findings reveal distinct pre-constitutive defense systems in two species consisting in an up-regulation of genes and primary metabolites involved in plant defense responses. These responses could be constitutively activated in V. rupestris opening new insights for sustainable viticulture through improved breeding programs.